Analisis Hidrograf Satuan Sintetik Snyder dan Soil Conservation Service (SCS) Daerah Aliran Sungai Klawoguk - Arpan Pujianto Simak; Anif Farida; Achmad Rusdi; Hendrik Pristianto (Pelantar Press, 2025)
Klawoguk Watershed is one of the watersheds in the Sorong City area. The problem in the watershed is the absence of hydrological data or automatic water level recording (AWLR) data. The purpose of this study was to determine and compare the parameters of the Snyder synthetic unit hydrograph and the SCS synthetic unit hydrograph. The methods used in this study are the Snyder Synthetic Unit Hydrograph and the SCS Synthetic Unit Hydrograph. The results of the study showed that the parameters obtained from the analysis results of HSS Snyder were tp 3,267 hours, te 0,594 hours, Tp 3,767 hours, Qp 1,193 m3/sec, and the parameters obtained from the analysis results of HSS SCS were TL 3.992 hours, Tp 4.492 hours, Qp 1.389 m3/sec, so it can be seen that the peak discharge value of HSS Snyder is lower than the peak discharge of HSS SCS and the time required for the decrease in peak discharge of HSS Snyder is longer than that of HSS SCS.